Exploring critical dimensions for measuring service quality in government to employee. (27th November 2020) - Janita, Mª Soledad; Miranda, F. Javier
The main objective of this article is to identify the dimensions or characteristics that a university service portal must have if it is to be considered by its employees as high quality. To achieve this objective, a qualitative study was carried out using the Delphi method and there was a subsequent quantitative study among academics from different Spanish universities. The four dimensions identified in our study confirm that e-service quality, in the Spanish university context, is a multidimensional construct. We are aware that universities have limited resources, so the managers of these service portals must pay special attention to those dimensions that are most important to users.